Galectin-3 regulates hepatic progenitor cell expansion during liver injury. Issue 2 (16th May 2014) - Hsieh, Wei-Chen; Mackinnon, Alison C; Lu, Wei-Yu; Jung, Jonathan; Boulter, Luke; Henderson, Neil C; Simpson, Kenneth J; Schotanus, Baukje; Wojtacha, Davina; Bird, Tom G; Medine, Claire N; Hay, David C; et al.
Abstract : Objective: Following chronic liver injury or when hepatocyte proliferation is impaired, ductular reactions containing hepatic progenitor cells (HPCs) appear in the periportal regions and can regenerate the liver parenchyma. HPCs exist in a niche composed of myofibroblasts, macrophages and laminin matrix. Galectin-3 (Gal-3) is a β-galactoside-binding lectin that binds to laminin and is expressed in injured liver in mice and humans. Design: We examined the role of Gal-3 in HPC activation. HPC activation was studied following dietary induced hepatocellular (choline-deficient ethionine-supplemented diet) and biliary (3, 5-diethoxycarbonyl-1, 4-dihydrocollidine supplemented diet) injury in wild type and Gal-3(−/−) mice. Results: HPC proliferation was significantly reduced in Gal-3(−/−) mice. Gal-3(−/−) mice failed to form a HPC niche, with reduced laminin formation. HPCs isolated from wild type mice secrete Gal-3 which enhanced adhesion and proliferation of HPCs on laminin in an undifferentiated form. These effects were attenuated in Gal3(−/−) HPCs and in wild type HPCs treated with the Gal-3 inhibitor lactose. Gal-3(−/−) HPCs in vitro showed increased hepatocyte function and prematurely upregulated both biliary and hepatocyte differentiation markers and regulated cell cycle genes leading to arrest in G0 /G1 . Conclusions: We conclude that Gal-3 is required for the undifferentiated expansion of HPCs in their niche in injured liver.